Alterations of monocyte NF-κB p65/RelA signaling in a cohort of older medical patients, age-matched controls, and healthy young adults - Juliette Tavenier; Line Jee Hartmann Rasmussen; Morten Baltzer Houlind; Aino Leegaard Andersen; Inge Panum; Ove Andersen; Janne Petersen; Anne Langkilde; Jan O. Nehlin (Immunity & Ageing, 2020)
Abstract Background Altered monocyte NF-κB signaling is a possible cause of inflammaging and driver of aging, however, evidence from human aging studies is sparse. We assessed monocyte NF-κB signaling across different aging trajectories by comparing healthy older adults to older adults with a recent emergency department (ED) admission and to young adults. Methods We used data from: 52 older (≥65 years) Patients collected upon ED admission and at follow-up 30-days after discharge; 52 age- and sex-matched Older Controls without recent hospitalization; and 60 healthy Young Controls (20–35 years). Using flow cytometry, we assessed basal NF-κB phosphorylation (pNF-κB p65/RelA; Ser529) and induction of pNF-κB following stimulation with LPS or TNF-α in monocytes. We assessed frailty (FI-OutRef), physical and cognitive function, and plasma levels of IL-6, IL-18, TNF-α, and soluble urokinase plasminogen activator receptor. Results Patients at follow-up were frailer, had higher levels of inflammatory markers and decreased physical and cognitive function than Older Controls. Patients at follow-up had higher basal pNF-κB levels than Older Controls (median fluorescence intensity (MFI): 125, IQR: 105–153 vs. MFI: 80, IQR: 71–90, p < 0.0001), and reduced pNF-κB induction in response to LPS (mean pNF-κB MFI fold change calculated as the log10 ratio of LPS-stimulation to the PBS-control: 0.10, 95% CI: 0.08 to 0.12 vs. 0.13, 95% CI: 0.10 to 0.15, p = 0.05) and TNF-α stimulation (0.02, 95% CI: − 0.00 to 0.05 vs. 0.10, 95% CI: 0.08 to 0.12, p < 0.0001). Older Controls had higher levels of inflammatory markers than Young Controls, but basal pNF-κB MFI did not differ between Older and Young Controls (MFI: 81, IQR: 70–86; p = 0.72). Older Controls had reduced pNF-κB induction in response to LPS and TNF-α compared to Young Controls (LPS: 0.40, 95% CI: 0.35 to 0.44, p < 0.0001; and TNF-α: 0.33, 95% CI: 0.27 to 0.40, p < 0.0001). In Older Controls, basal pNF-κB MFI was associated with FI-OutRef (p = 0.02). Conclusions Increased basal pNF-κB activity in monocytes could be involved in the processes of frailty and accelerated aging. Furthermore, we show that monocyte NF-κB activation upon stimulation was impaired in frail older adults, which could result in reduced immune responses and vaccine effectiveness.